Towards a typology of cross-media news consumption: a qualitativequantitative synthesis - Schrder, Kim Christian and Kobbernagel, Christian (Northern Lights: Film & Media Studies Yearbook, 2010)
The article presents the first version of a methodologically innovative typology of people's use and experience of news, across different media platforms. Theoretically, the article is based on the modernized version of Jrgen Habermas's theory of the public sphere, which is sometimes labelled theory of cultural citizenship, or civic agency. We observe the citizen-consumers' selection from the available news media through the theoretical lens of perceived worthwhileness, which consists of seven dimensions that aggregate to condition an individual's portfolio of news media in everyday life. The empirical investigation uses an integrated qualitative-quantitative method, resulting in a typology of cross-media news consumption with seven user types, which is compared with the Pew 2008 study of news consumption in the United States.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9ubC44LjExNV8x